A survey of diseases in captive bearded dragons: a retrospective study of 529 patients - Schmidt-Ukaj, S.; Hochleithner, M.; Richter, B.; Hochleithner, C.; Brandstetter, D.; Knotek, Z. (Veterinarni medicina, 2017)
The aim of this clinical retrospective study was to analyse the prevalence of common disorders in 529 captive bearded dragons that were presented to three exotic animal clinics in Central Europe (Austria and Czech Republic) over a period of three years. A diagnosis was made on the basis of the presenting clinical signs and physical examination in 30.8% of the cases, whereas various additional diagnostic tests were performed in the other cases (69.2%). These included diagnostic imaging (radiography, ultrasound and computed tomography), examination of faecal samples for the presence of parasites, a blood-profile analysis, histological, as well as bacteriological and mycological examinations and necropsy. Gastrointestinal diseases (42.67%) like endoparasitism, constipation, sand ingestion, tympany and meteorism were the most common disorders. In 51.92% of the cases of constipation, endoparasites were present, whereas in 38.46% of the cases of constipation, metabolic bone diseases and imbalances in calcium and phosphorus levels were detected. Most of the analysed faecal samples (83.27%) were positive for the presence of endoparasites (48.7% pinworms, 25.39% coccidians and 16.06% flagellates). Dermatological problems (22.4%) contained skin tumours, which were observed in adult lizards (age range from three to eight years) and included spindle cell tumour on the eyelid, as well as spindle cell sarcoma, squamous cell carcinoma and melanoma on the trunk. Osteodystrophy, limb fractures and various types of necrosis on the limbs and tail were frequently observed musculoskeletal disorders (18.93%). Over half of all animals (57.14%) that underwent a blood test, showed a deviation in the calcium-phosphorus ratio, 63.98% showed hypocalcaemia and 26.71% hyperphosphataemia. Diseases of the urogenital system (9.47%) included renal diseases and dystocia. Neoplastic diseases besides skin tumours included two cases of leukaemia in 4-year-old bearded dragons, one of these with lymphoma in kidneys, lungs and liver and one ganglioneuroma in the body cavity of a bearded dragon of unknown age. Orthopaedic surgeries were most frequently performed to amputate the limbs or tail, whereas soft-tissue surgeries most often included the treatment of skin wounds and correction of cloacal prolapse, in addition to ovariectomy, salpingotomy or salpingectomy in female bearded dragons. Similar to the situation in Australia and the USA, infectious as well as non-infectious diseases are common in captive bearded dragons in Central Europe. Due to the high occurrence of endoparasitism, skin diseases and metabolic bone diseases in this present study, regular veterinary controls in bearded dragons including parasitological faecal examinations and optimisation of feeding and housing are necessary to improve the standard of health of bearded dragons kept as pet lizards in Europe.
Keywords: agamid lizards; captive reptiles; infectious diseases; metabolic diseases